Characterization of the etiological structure and genotypically determined phenotypic resistance to carbapenems of infectious complications leading pathogens in critically ill patients - O. A. Nazarchuk (Zaporožskij Medicinskij Žurnal)
The aim is to investigate the genotypically determined phenotypic resistance to carbapenems of gram-negative microorganisms isolated from patients with critical states.